Systematic review: exploring the association between facial crease of adult female based on the application of cosmetic skin care product - Bahsir, Nur Afiqah Abdul (2020)
This study is carried out to analyse the changes of facial crease among female based on the usage of skin care product. The formations of facial crease, wrinkle or fine line manifest as early 30 years old. The facial crease changes are caused by intrinsic and extrinsic factor. The evolution of anti-aging skin care product that contains active ingredients will be able to help in delaying of skin aging process. There are two types of data collection involved in this study which is primary and secondary data collection. Both of these data give signif icant information in this study. However, this study focuses on the secondary data collection where the method used for secondary data was systematic review. A literature search of PubMed, Google Scholar and Science Direct was conducted through July 2020 using keywords including "skin aging", "facial crease", "facial wrinkle", "anti-aging cosmetic", "anti-aging active ingredient", and "aging women". The selection of article was select based on the inclusion criteria and exclude any article does not relate to the objective of the study. From the search method, a total of 2559 titles were found. After removing duplications, irrelevant title and abstract, the number of articles were reduced to 150. Out of the 150 titles, 17 tittles were seen suitable for inclusion in this review. The studies show that the relation between facial crease and anti-aging cosmetic where active ingredient in anti-aging cosmetic generally plays an importance role to delay the formation of crease or wrinkle.